Absence of adverse effects following administration of piperine in the diet of Sprague-Dawley rats for 90 days. (October 2018) - Bastaki, Maria; Aubanel, Michel; Bauter, Mark; Cachet, Thierry; Demyttenaere, Jan; Diop, Maodo Malick; Harman, Christie L.; Hayashi, Shim-mo; Krammer, Gerhard; Li, Xiaodong; Llewellyn, Craig; Mendes, Odete; et al.
Abstract: Piperine ( E, E- ) is a naturally occurring pungent and spicy constituent of black pepperand is also used as an added flavoring ingredient to foods and beverages. Piperine has been determined safe under conditions of intended use as a flavoring substance by regulatory and scientific expert bodies. While concurring with the Joint FAO/WHO Expert Committee on Food Additives (JECFA) and Flavor and Extract Manufacturers Association (FEMA) Expert Panel on the safety of piperine, the European Food Safety Authority (EFSA) requested additional toxicological data. The results of a 90-day GLPcompliant dietary study, conducted in Sprague-Dawley rats at target doses of 0, 5, 15, or 50 mg/kg bw/day, to respond to this request are presented herein. No adverse effects were found attributable to ingestion of piperine. Statistically significant changes in food consumption, body weight gain, and plasma cholesterol levels were not considered adverse as discussed in this paper. Therefore, the oral no-observed-adverse-effect level (NOAEL) was determined to be the highest dose tested of 50 mg/kg bw/day. EFSA derived a lower NOAEL of 5 mg/kg bw/day based on increased plasma cholesterol levels which still affords an adequate margin of safety of over 48, 000 and concluded that piperine is not of safety concern. Highlights: GLP-compliant 90-day study of piperine following OECD guideline. Piperine produces no adverse effects in rats fed diets containing up to 3600 ppm of added flavor for 90 days. A threshold of toxicity (NOAEL) of 50 mg/kg bw/day is proposed for piperine.